Smart Egg Sorting Monitoring System Based on Internet of Things - Fa'is Nur Farid; Ari Endang Jayati; Elfira Nureza Ardina (CV. Akira Java Bulu, 2026)
The poultry farming industry plays an important role in supplying affordable animal protein. However, egg sorting processes are still commonly performed manually, resulting in inefficiency and inconsistent classification. This research proposes an Internet of Things (IoT)-based egg sorting monitoring system utilizing an ESP32 microcontroller integrated with a load cell sensor for weight measurement and an LDR sensor for shell quality evaluation. The system automatically classifies eggs and transmits monitoring data in real time to the Thinger.io web platform. Experimental results demonstrate that the proposed system achieves high classification accuracy with minimal measurement error. The implementation of this system indicates that IoT technology can significantly enhance efficiency, accuracy, and digital data accessibility in poultry farming.